Alternative uses for vinasse, an alcohol industry residue. A review - Tauk, S. M. (Taylor & Francis, 1982)
Recent studies on the recycling of vinasse, its potential use in agriculture and possible environmental problems resulting from the use and disposal of this residue are reviewed.
Keywords: alcohol; agriculture; fermentation; prevention; review; theoretical study; therapy; vinasse; waste management